Implementation of Muhasabah Technique in Developing Resilience of Children in Conflict with the Law - Khoirun Nisa Rahayu; Ulfa Fauzia Argestya (TAUJIHAT: Jurnal Bimbingan Konseling Islam, 2025)
This study focuses on children in conflict with the law. The purpose of this study is to analyse the application of the muhasabah technique in building the resilience of children in conflict with the law at the Class 1 Surakarta Correctional Centre. This study uses a qualitative method with a descriptive approach. The selection of subjects used a purposive sampling technique with four community counsellors who had handled cases of street violence with child perpetrators and applied the muhasabah technique. Data collection used observation, interviews, and documentation. The results of the study showed that the success of this technique is highly dependent on the relationship between community counsellors and children in conflict with the law. The stages applied include: building good relationships with the children and parents, exploring the chronology of the case through open and closed questions, inviting the children to reflect on their actions and the consequences received, and providing reflective tasks to encourage changes in mindset. The results of implementing this technique have been proven to help children in conflict develop self-awareness, build more positive social relationships, and control emotions, thus contributing to the development of their resilience.